Chemical communication, sexual selection, and introgression in wall lizards. (13th September 2017) - MacGregor, Hannah E. A.; Lewandowsky, Rachel A. M.; d'Ettorre, Patrizia; Leroy, Chloé; Davies, Noel W.; While, Geoffrey M.; Uller, Tobias
Abstract: Divergence in communication systems should influence the likelihood that individuals from different lineages interbreed, and consequently shape the direction and rate of hybridization. Here, we studied the role of chemical communication in hybridization, and its contribution to asymmetric and sexually selected introgression between two lineages of the common wall lizard ( Podarcis muralis ). Males of the two lineages differed in the chemical composition of their femoral secretions. Chemical profiles provided information regarding male secondary sexual characters, but the associations were variable and inconsistent between lineages. In experimental contact zones, chemical composition was weakly associated with male reproductive success, and did not predict the likelihood of hybridization. Consistent with these results, introgression of chemical profiles in a natural hybrid zone resembled that of neutral nuclear genetic markers overall, but one compound in particular (tocopherol methyl ether) matched closely the introgression of visual sexual characters. These results imply that associations among male chemical profiles, sexual characters, and reproductive success largely reflect transient and environmentally driven effects, and that genetic divergence in chemical composition is largely neutral. We therefore suggest that femoral secretions in wall lizards primarily provide information about residency and individual identity rather than function as sexual signals.